Road to Nowhere : Transitions to Adulthood and the New Social Vagrants in post-1997 South Korea - Gouiffes, Perrine (My University, 2018)
This thesis explores the transitions into adulthood undertaken by the South Korean youth born during the 1997 Asian Economic Crisis, which urged South Korea to accept and implement radical economic and social reforms following the recommendations of the International Monetary Fund. These reforms had a prominent impact on the state of the labour market, introducing a precarity as-yet unknown, and reinforcing heightened competition in all aspects of society. The devaluation of university diplomas and the difficulty to undertake ‘normal’ housing and employment careers that followed impacted the transitions into adulthood of a youth for whom the attainment of independence allowing them to produce their own cultural, social, and material capital is increasingly difficult. Thus, this thesis aims to understand the effect the survival strategies put in place by this generation to cope with a collapsing structure of opportunity might have on social reproduction and the upkeep of the social model in South Korea. Secondary research was used to establish the socio-economic context in which the studied youth evolve, and to understand the main theoretical mechanisms behind the transitions into adulthood, downward social mobility, and the devaluation of university diplomas. Primary research was conducted through qualitative semi-structured and in-depth interviews with South Korean informants, analysed through narrative analysis as a mean to established careers and biographies, while the generational theory serves as the basis for data analysis, complemented by participant observations gathered during the same field research conducted in 2017 in Seoul. The results indicate that the known processes of social reproduction have been damaged, and that South Korean youth now follow proacted patterns of transition, which could precede the systemisation of downward social mobility across generation and open the way for a collapse dynamic to occur in South Korean society, if left unchecked. Moreover, results testified of an acute anxiety in regard to the future, coupled with a certain apathy and disillusionment, making up the locus of the social vagrant identity embraced by the informants. However, further research should be conducted to establish how these proacted transitions and their impact on social reproduction will indeed affect future generations.
Keywords: transitions to adulthood, downward social mobility, neoliberalism, social reproduction, Asian economic crisis, South Korea